A new model for Sb deposition in the French Massif Central based upon thermodynamic modeling of the mineralizing fluid - Van Hinsberg, V; Zinngrebe, E; de Wijs, C; Vriend, S (2003)
A new model for antimony (Sb) deposits in the Haut-Allier area of the French Massif Central is proposed, based on thermodynamic modeling of the mineralizing fluid. The Sb deposits in the research area contain stibnite and berthierite as Sb minerals, and occur in veins crosscutting gneiss lenses. The surrounding schist host rock is non-mineralized. Thermodynamic modeling of the ore-fluid shows that no Sb minerals will precipitate if the fluid is buffered by alteration reactions in the host rock. However, brittle fractures, developed in the gneiss lenses during uplift, channelize the fluid flow, which eventually results in the loss of contact with the buffering environment. With lowering temperatures the Sb solubility sharply decreases in this unbuffered fluid and Sb-minerals precipitate. The schists continue to allow pervasive fluid flow instead, buffering the fluid outside the stibnite stability field and no Sb deposits are therefore present. © 2003 Elsevier Science B.V. All rights reserved.